Optimizing Solar Thermal Energy Systems for Integration in Industrial Processes A Case Study of Mewaholeo Industries Sdn Bhd Oil Palm Refinery in Malaysia - Adam Rasyid Sidiqi; Zarina Ab Muis (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
Fossil fuels contribute to global warming and climate change. Solar energy, a renewable and safe energy source, is a promising alternative. Solar thermal energy (STE) can be used in various sectors to produce thermal or electrical energy from the sun. In Malaysia, electricity is cheaper, making it less appealing to switch to renewable energy. This study aims to explore the potential of solar thermal heat systems in industrial processes in Malaysia, focusing on the oil palm refinery Mewaholeo Industries Sdn Bhd. The main challenge is the high capital investment and varying efficiencies of solar thermal systems, which depend on technical specifications and environmental factors. To determine the optimal specifications for solar thermal system installation, this study will examine the process flow, propose a solar thermal system design, collect data, and integrate solar thermal energy. The best collector type, number of collectors, and solar thermal design will be analyzed using an Excel tool called Solar Heat Industry Process (SHIP) for performance and financial evaluation.